(untitled) - Burton, L. DeVere (Clifton Park, NY, 2007)
The book covers the principles and practices of forest management, integrated with an applied science approach. The processing of wood and forest products, the economic impact of forests on the U.S. economy, and Current laws and regulations that govern the use of forests in addition to government historical events and policies that have influenced forest management practices are included
Keywords: Forests and forestry,Forest management,Rừng và lâm nghiệp,Quản lý rừng; North America,United States,Bắc Mỹ,Hoa Kỳ